Kinerja Program Studi Administrasi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta - Sheffany Nur Layla; Rugaiyah Rugaiyah; Desi Rahmawati (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2017)
The improving of performance in educational institution is expected to produce agood output. Many things must be prepared and have good performance to achieve thequality institution. This study focuses on the evaluation of the implementation of theStandards and Procedures Accreditation of Undergraduate Studies at Higher Educationlevel in Education Administration Studies Program Faculty of Education, UniversitaNegeri Jakarta. The scope of study is limited to the evaluation of the implementation ofstandards and procedures for accreditation.This study uses Discrepancy Evaluation Model (DEM) as model evaluation. Itevaluates the gaps of program that is based on intermediate state which is expected in theplan with that generated in the implementation of the program. Evaluation of the gap isintended to determine the level of compatibility between the standards prescribed in theprogram with the actual appearance of the program. The data source is data offinancing,insfrastructure, information system, research, community service andcooperation in year 2013-2015.sThese results indicate that; (1) the performance component on financing aspects,the aspect of financing is not directly managed by the study program. (2) the existingcomponents of the infrastructure shows the percentage of achievement in the category ofgood. (3) the component information system shows the percentage of achievement in thecategory of good. (4) component research, community service and cooperation shows thepercentage in the category of pretty good achievement. Based on the acquisition of thefour components of the above, the performance Educational Administration Faculty ofEducation UNJ aspects of financing, infrastructure, information systems, research,service and cooperation demonstrated has good category.